Molecular mechanism of Huaihuasan in treatment of ulcerative colitis based on network pharmacology and molecular docking - Yi Wu; Xiaokun Yang; Guiwei Li; Xinqiao Liu (Elsevier, 2021)
Background: Huaihuasan (HHS) is a Traditional Chinese Medicine formula for ulcerative colitis (UC). However, the pharmacology and molecular mechanism of HHS on ulcerative colitis still unclear. Purpose: Implement network pharmacology and molecular docking for revealing main active components of Huaihuasan against ulcerative colitis and to explore therapeutic mechanism. Study design and methods: TCMSP, PubChem, Swiss Target Prediction and GeneCards are utilized to search the active components and effective targets of HHS and ulcerative colitis. The co-targets between HHS and ulcerative colitis are obtained by Draw Venn Diagram. STRING database is intended to draw the PPI network. To obtain the core targets, topological analysis is used by Cytoscape 3.7.2. GO and KEGG enrichment pathway analysis was performed to Metascape platform, and molecular docking through Autodock Vina 1.1.2 finished. Result: 21 active components with 211 effective targets of HHS, and 2325 effective targets of ulcerative colitis were screened. The Venn analysis was contained 89 co-targets. Enrichment analysis showed that HHS played a role in pathways in cancer, proteoglycans in cancer, PI3K-Akt signaling pathway, etc. Finally, two targets (AKT1 and EGFR) were successfully docked with 3 core components (isorhamnetin, kaempferol, quercetin), respectively. Conclusion: HHS can act on multiple targets through multi-pathway, so as to perform its therapeutic role in ulcerative colitis.